LA SEGURIDAD y CONFIAbILIDAD DE LOS DATOS EN LOS SISTEMAS DE INFORMACIÓN COMpUTARIzADA - Rivera León, Felix Armando (2013)
A rapid multiplication of the terminal devices and the growth of distributed systems add new dimensions to the auditor task to ensure you have a safe system of PD. Although there is not perfect system of data communication, several design concepts and requirements that auditors should understand to simplify their assessments and to allow them reasonable recommendations.